Immunological Indications of Serum From the California Red Worm - Annakulovna, Nurova Zamira; Urmanovna, Urazova Zarina; Dilshod o’g’li, Odilov Ramziddin; Nodirovna, Hamidbayeva Mushtariy; Ulug’bek qizi, Xasanova Sevinch (European Journal of Life Safety and Stability (2660-9630), 2022)
In our ongoing scientific research, the analysis of laboratory methods of serum obtained from the California red worm was checked and searched for immunological indicators using reagents and reagents. The main object of this research is the Californian red worm and the technology and geology of its cultivation. Investigations were carried out on the basis of hematological indicators in special analyzers and distillers. The purpose of this investigation is to produce lymph fluid in all organs where the lymph node is located, and under its influence, this organ is a substitute for blood, which is characteristic of blood fluid, and this organ stimulates the immune system. Antibodies are developed against the foreign body. This is done directly in cooperation with protection, regulator, and operator gene. As a result, a person's immune system increases, immunized is stimulated, a person's activity increases, ATF synthesis occurs, energy is formed, he does not become drowsy, and hemopoiesis of a person increases